Multi-Year Field Evaluation of Fluorinated Nematicides Against Meloidogyne incognita in Carrots - Becker, J O (Plant disease, 2019)
California grows approximately 80% of the U.S. carrot production. The primary production challenges derive from root-knot nematodes (Meloidogyne spp.). Between 2013 and 2016, we evaluated three novel fluorinated nonfumigant nematicides in five field trials. Fluensulfone, fluopyram, and fluazaindolizine were applied as product-ready formulations at various rates, dates, and formulations. They were rated for their efficacy against the Southern root-knot nematode (M. incognita), their ability to mitigate nematode-caused crop damage, and potential to produce marketable carrot yield under high disease pressure. All trials were conducted in randomized complete block designs in M. incognita-infested, sandy-loam fields. Soil population of M. incognita at seeding and harvest, midseason plant vigor and fibrous root galling, harvest taproot galling, and marketable carrot yield were analyzed by ANOVA. Midseason gall ratings were indicative of disease ratings at harvest. All fluazaindolizine and fluensulfone treatments reduced at-harvest galling compared with the untreated controls. Fluopyram resulted in less galling but did not sufficiently protect the lower part of the taproot. Overall, fluazaindolizine at 2.24 kg/ha resulted in the most consistent and highest marketable carrot yield, followed by fluensulfone at 2.95 kg/ha. Both fluazaindolizine and fluensulfone will likely provide effective and target-selective crop protection against root-knot nematodes in fresh carrot production